Demographic consequences of foraging ecology explain genetic diversification in Neotropical bird species. (3rd January 2021) - Miller, Matthew J.; Bermingham, Eldredge; Turner, Benjamin L.; Touchon, Justin C.; Johnson, Andrew B.; Winker, Kevin
Abstract: Despite evidence that species' traits affect rates of bird diversification, biogeographic studies tend to prioritise earth history in Neotropical bird speciation. Here we compare mitochondrial genetic differentiation among 56 co‐distributed Neotropical bird species with varying ecologies. The trait 'diet' best predicted divergence, with plant‐dependent species (mostly frugivores and nectivores) showing lower levels of genetic divergence than insectivores or mixed‐diet species. We propose that the greater vagility and demographic instability of birds whose diets rely on fruit, seeds, or nectar  known to vary in abundance seasonally and between years  relative to birds that eat primarily insects, drives episodic re‐unification of otherwise isolated populations, resetting the divergence 'clock'. Testing this prediction using coalescent simulations, we find that plant‐dependent species show stronger signals of recent demographic expansion compared to insectivores or mixed‐diet species, consistent with this hypothesis. Our study provides evidence that localised ecological phenomena scale up to generate larger macroevolutionary patterns. Abstract : Despite evidence that species' traits affect rates of bird diversification, biogeographic studies tend to prioritize earth history in Neotropical bird speciation. We predict that species with plant‐based diets, which must disperse to find seasonal and spatially variable resources will show lower patterns of genetic structure than birds species that feed primarily on arthropods, which are a more stable food source. Plant‐dependent species show lower genetic divergence and stronger signals of recent demographic expansion compared to insectivores or mixed‐diet species, consistent with this prediction, providing evidence that localized ecological phenomena may scale up to generate macroevolutionary patterns.